Foreword - Aksela, Maija (LUMAT-B: International Journal on Math, Science and Technology Education, 2016)
Chemistry teaching and learning is one of the areas of focus in research in the Department of Chemistry in the University of Helsinki. Research creates a base for supporting the understanding of chemistry and for the development of good-quality chemistry teaching from basic education to higher education and to teacher education. With the use of evidence-based teacher education in chemistry, we support chemistry teaching and its development communally. The characteristic of our research is researching in the interfaces of formal, non-formal and informal teaching. In honor of the 15th Anniversary of the Unit of Chemistry Teacher Education in Department of Chemistry, this book is published, where our research is presented, and specialists in research on chemistry education, who have grown up in the unit are brought out. The writers of these articles are PhDs, who have graduated from the unit, and doctoral students. The articles have been peer reviewed communally. In the articles, the central concepts of topics are described briefly, the benefits and challenges from the point of view of previous research and the writer's own research and as well it is brought out, how teachers are able to exploit information in chemistry teaching. The articles can be used freely in teaching, teacher training and research. At the end of each article, you can find information on the writers, about their research and specializations concerning their education as well as their contact details. Our specialists are accessible in different education, development and research plans, nationally and internationally.